Changes in condom use behaviours among clients of female sex workers in China. Issue 5 (3rd June 2009) - Lau, J T F; Wan, S P; Yu, X N; Cheng, F; Zhang, Y; Wang, N; Zhang, L; Zhang, J
Abstract : Background: Clients of female sex workers (CFSWs) are at risk for HIV transmission; relevant surveillance and interventions for this vulnerable group are scarce. The China-UK HIV/AIDS Prevention and Care Project launched an enhanced intervention programme involving peer education, seminars, testing services and social gatherings and so forth, and two behavioural surveillance studies (BSS) targeting CFSWs in Suining, Sichuan. Methods: Two cross-sectional BSS (a baseline survey and an evaluative survey) were conducted in September 2005 and May 2006, respectively. In total, 356 and 372 respondents who patronised some low-end sex services were interviewed by peer interviewers. Another triangulation condom audit exercise was conducted in June 2006. Results: Prevalence of respondents using at least one prevention service increased from 50.3% in 2005 to 68.5% in 2006 (AOR = 2.2). Respondents of the evaluative survey compared with their counterparts of the baseline survey had lower prevalence of inconsistent condom users in the last 6 months (44.1% vs 77.0%; AOR = 0.2) and higher prevalence of condom use in the last episode of commercial sex (78.0% vs 41.5%; AOR = 4.9). The triangulation audit showed that condoms were used by 73.8% of CFSWs. The multivariate analysis shows that year of study (OR = 0.3), self-reported sexually transmitted disease symptoms (OR = 2.9), use of face-to-face counselling services (OR = 0.5) and so forth were significantly associated with inconsistent condom use during commercial sex in the last 6 months. Conclusions: Condom use and service use behaviours changed in the study population over a time period when an enhanced intervention programme was implemented. Such effective programmes may be applied to other locations in China.